The economics of risky health behaviors - John Cawley; Christopher J. Ruhm (Institute for the Study of Labor (IZA), 2011)
Risky health behaviors such as smoking, drinking alcohol, drug use, unprotected sex, and poor diets and sedentary lifestyles (leading to obesity) are a major source of preventable deaths. This chapter overviews the theoretical frameworks for, and empirical evidence on, the economics of risky health behaviors. It describes traditional economic approaches emphasizing utility maximization that, under certain assumptions, result in Pareto-optimal outcomes and a limited role for policy interventions. It also details nontraditional models (e.g. involving hyperbolic time discounting or bounded rationality) that even without market imperfections can result in suboptimal outcomes for which government intervention has greater potential to increase social welfare. The chapter summarizes the literature on the consequences of risky health behaviors for economic outcomes such as medical care costs, educational attainment, employment, wages, and crime. It also reviews the research on policies and strategies with the potential to modify risky health behaviors, such as taxes or subsidies, cash incentives, restrictions on purchase and use, providing information and restricting advertising. The chapter concludes with suggestions for future research.
urn:nbn:de:101:1-201106013425
Keywords: I1; I20; I18; D01; H2; D1; D6; D03; D87; D83; J1; Q18; I24; 330; health behaviors; alcohol; tobacco; smoking; drugs; obesity; diet; food; physical activity; public health; public policy; taxation; subsidies; addiction; externalities; advertising; information; behavioral economics; neuroeconomics; human capital; education; prices; sex; income; time preference; peers; bounded rationality; medical costs; employment; wages; crime; hyperbolic discounting